Thymic stromal lymphopoietin induces platelet mitophagy and promotes thrombosis in Kawasaki disease. (7th November 2022) - Fu, Lanyan; MacKeigan, Daniel Thomas; Gong, Qing; Che, Di; Xu, Yufen; Pi, Lei; Sun, Chaonan; Yu, Hongyan; Chen, Kaining; Zhou, Huazhong; Jiang, Zhiyong; Wang, Zhouping; et al.
Summary: Kawasaki disease (KD) is an acute systemic vasculitis primarily affecting infants and children. Activated platelets predispose patients to coronary artery structural lesions that may lead to thrombotic cardiovascular events. To discover potential proteins underlying platelet activation in KD, we conducted a protein chip assay of 34 cytokines and discovered thymic stromal lymphopoietin (TSLP) was aberrantly expressed, which remained elevated after intravenous immunoglobulin G (IVIG) treatment and during convalescence in KD patients in comparison to healthy controls. Enzyme‐linked immunosorbent assay (ELISA) corroborated the upregulation of TSLP in KD patients, which was exacerbated in convalescent patients complicated with thrombosis. TSLP receptors on platelets were also significantly upregulated in KD patients complicated with thrombosis. Platelet activation, apoptosis, and mitochondrial autophagy (mitophagy) were increased in convalescence KD patients complicated with thrombosis. In vitro, TSLP induced platelet activation and platelet mitophagy in healthy blood donors, as observed in KD patients. TSLP, similar to mitophagy agonist carbonyl cyanide 3‐chlorophenyl hydrazone (CCCP), promoted thrombosis, which was attenuated by the mitophagy inhibitor Mdivi‐1. Co‐immunoprecipitation in TSLP‐treated platelets revealed TSLP receptor (TSLPR) bound to mitophagy regulators, Parkin and Voltage Dependent Anion Channel Protein 1 (VDAC1).Thus, our results demonstrated that TSLP induced platelet mitophagy via a novel TSLPR/Parkin/VDAC1 pathway that promoted thrombosis in KD. These results suggest TSLP as a novel therapeutic target against KD‐associated thrombosis. Abstract :